Cognitive Flexibility and Pro–Environmental Behaviour: A Multimethod Approach. Issue 4 (July 2019) - Lange, Florian; Dewitte, Siegfried
While cognitive flexibility has been hypothesized to relate to adaptive, long–term–oriented behaviour, empirical support for such a relationship is scarce. In the present article, we examine the role of cognitive flexibility as a correlate of long–term–oriented behaviour in the domain of environmental conservation. In a first study ( N = 143), we explored potential associations between multiple self–report scales and performance–based measures of cognitive flexibility and pro–environmental behaviour. Based on its results, we conducted a pre–registered confirmatory study ( N = 264) focusing on the most promising correlations found in our exploratory study. This study generated conclusive support for a positive medium–sized correlation between cognitive flexibility and pro–environmental behaviour. Exploratory hierarchical regression analyses further revealed that cognitive flexibility accounted for a small portion of variance in pro–environmental behaviour above and beyond the Big Five. While appearing robust on the level of self–reports, the relationship between cognitive flexibility and pro–environmental behaviour did not reliably extend to the level of performance tasks, possibly because of their relatively specific scope. These results illustrate the contribution of cognitive flexibility to understanding individual differences in long–term–oriented, pro–environmental behaviour. © 2019 European Association of Personality Psychology